Pengaruh Disiplin Kerja dan Budaya Organisasi Terhadap Kinerja Pegawai Pada Kantor Pertanahan Kabupaten Gianyar (WidyaAmrita: Jurnal Manajemen, Kewirausahaan dan Pariwisata, 2023)
There are concerns and findings related to work discipline issues and organizational culture in an effort to improve and improve employee performance in accordance with the purpose of this study to determine the influence of work discipline and organizational culture on the benefits of Gianyar Kantor District Employees. The population in this study consisted of all employees of the Gianyar Regency Land Office which amounted to 158 people. The number of samples in the study was 61 employees. The sample determination method in this study used proportional random sampling techniques. Data collection is carried out through observation, interviews, documentation, literature studies and questionnaires. The analytical techniques used are classical hypothesis tests, multiple linear regression analysis, determination analysis and hypothesis tests. The results showed that work discipline and organizational culture had a significant partial and simultaneous effect on the performance of employees of the Gianyar Regency Land Office.